Penerapan Blockchain untuk Transparansi RKAT dan KAK di SIPIM UNISR - Kholil, Moenawar; Sutikno, Arif; Fathona, Rina Robiulana (Universitas Boyolali, 2026)
Budget management in higher education requires transparency, accountability, and reliable audit mechanisms to prevent undocumented changes and ensure traceability of financial decisions. This study proposes and implements a permissioned blockchain event ledger integrated with the Leadership Information System (SIPIM) at Universitas Slamet Riyadi Surakarta to enhance the integrity of RKAT and KAK processes. The research adopts a design science research approach by designing a sidecar architecture that preserves the existing relational database while adding an append-only cryptographic audit layer. Document integrity is ensured through SHA-256 hashing and hash-chaining mechanisms, while chain validity is evaluated using quantitative integrity metrics. Experimental testing was conducted under transaction loads of 100, 300, and 500 blocks, including controlled manipulation scenarios. Results show that the system maintains 100% chain validity under normal conditions and successfully detects inconsistencies after unauthorized modifications. Performance evaluation indicates that block formation time remains below 7 milliseconds, demonstrating minimal computational overhead. The findings confirm that integrating a permissioned blockchain as an audit layer can strengthen transparency and tamper-evident control without disrupting operational systems in higher education institutions.